Formas gerais do Teorema da Dominação de Pietsch - Gomes, Luiz Ancelmo Dias (2016)
In this work we study a general version of the Pietsch Domination Theorem, due to Pellegrino, Santos and Seoane-Sep´ulveda, that improves the unified version present in [3] and recovers known Pietsch Domination-type theorems where the unified approach seems not to work.